Bridging agriculture and food: Aqueous ozone treatment optimizes wheat flour chracteristics and dough rheology to enhance bread quality in Iranian cultivars - Elmira Bamyar; Seyed Hadi Peighambardoust; Mehrtash Ahsan Ghaziani (Journal of Agriculture and Food Research, 2025)
This study investigated the impact of aqueous ozone (AO) treatment during tempering on the physicochemical, rheological, and breadmaking properties of two Iranian wheat cultivars, Hamedan (weak) and Shiraz (strong), at 72 % and 90 % extraction rates. Wheat samples were treated with AO at 0, 2, 4, and 8 mg/L, and the resulting flours were analyzed. AO treatment significantly affected flour color, increasing whiteness, particularly at 8 mg/L. For example, the whiteness index increased significantly (p < 0.05) in 72 % extraction flour. Moderate AO concentrations (2–4 mg/L) improved gluten quality in the weak cultivar; the gluten index of W-72 increased from 52.6 % (control) to 58.1 % at 2 mg/L ozone, but higher concentrations deteriorated the gluten network, decreasing back to 52.8 % at 8 mg/L. Falling number increased with AO treatment, indicating reduced alpha-amylase activity. Farinograph analysis revealed that dough stability for S-72 increased from 5.95 min (control) to 6.95 min at 4 mg/L ozone, indicating a strengthened gluten network, while Extensograph data showed that at 8 mg/L ozone, resistance to extension (Rmax) for S-72 at 45 min decreased from 293 BU (control) to 281 BU, suggesting gluten weakening. Breadmaking results revealed that 2–4 mg/L AO improved loaf volume and height, especially in the strong cultivar (S-72 loaf volume: 211.7 ± 2.9 cm3 at 2 mg/L ozone vs. 190.5 ± 3.2 cm3 in the control, p < 0.05), but 8 mg/L negatively impacted crumb firmness, increasing it to 5.00 N on Day 3, as compared to 0.60–0.93N in all other ozone treatments (p < 0.05), and accelerated staling. These results highlight the potential of AO treatment to modify flour properties and bread quality, emphasizing the importance of optimizing AO dosage to avoid detrimental effects.